Current Understanding of Innate Immune Cell Dysfunction in Childhood Undernutrition - Bourke, Claire D.; Jones, Kelsey D. J.; Prendergast, Andrew J. (Frontiers in Immunology, 2019)
Undernutrition affects millions of children in low- and middle-income countries (LMIC) and underlies almost half of all deaths among children under 5 years old. The growth deficits that characterise childhood undernutrition (stunting and wasting) result from simultaneous underlying defects in multiple physiological processes, and current treatment regimens do not completely normalise these pathways. Most deaths among undernourished children are due to infections, indicating that their anti-pathogen immune responses are impaired. Defects in the body’s first-line-of-defence against pathogens, the innate immune system, is a plausible yet understudied pathway that could contribute to this increased infection risk. In this review, we discuss the evidence for innate immune cell dysfunction from cohort studies of childhood undernutrition in LMIC, highlighting knowledge gaps in almost all innate immune cell types. We supplement these gaps with insights from relevant experimental models and make recommendations for how human and animal studies could be improved. A better understanding of innate immune function could inform future tractable immune-targeted interventions for childhood undernutrition to reduce mortality and improve long-term health, growth and development.